Obrzęd zawarcia małżeństwa w nadzwyczajnej formie - Jakubiak, Tomasz (Ius Matrimoniale, 2014)
In Poland the Faithful of the Catholic Church, lay and ordained alike, are so much accustomed to in-church marriages that they perceive as valid only those where at least one party belongs to the Catholic Church and the marriage is contracted before the local ordinary, pastor, or a priest or deacon delegated by either of them, who assist, and before two witnesses. In fact the legislator envisages a couple of exceptions from the rule cited above. One of them is the possibility to contract the marriage validly and licitly before witnesses only. Ordo celebrandi Matrimonium does not give any suggestions how this extraordinary form of marriage should look like. The article tries to clarify this ambiguity.